(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2019)
Aim: To evaluate the transverse discrepancy in Class II div 2 malocclusion and normal occlusion. Also to test the hypothesis that models with class II div 2 malocclusions may have mean maxillary arch widths significantly smaller than those with normal occlusion. Thus the proposed study will generate interest among the orthodontists for further study over the transverse discrepancy of our patients and guide them to establish effective treatment strategy and their management. Materials and Methods : Cross sectional comparative study was carried out Department of Orthodontics & Dentofacial Orthopedics of Dhaka Dental College & Hospital, Dhaka with 100 sample was included in this study. Results: Maxillary intercanine, interfirst premolar and interfirst molar widths between normal occlusions and class II div 2 malocclusions were statistically significant.Maxillary measurements of class II div 2 malocclusion were smaller than normal occlusion. Mandibular intercanine, interfirst premolar and interfirst molar widths between Class II div 2 malocclusion and normal occlusions were statistically significant. Conclusion: This study helps in determining possible differences in the dental arch widths of Bangladeshi people in Class II-2 adults compared to adults with normal occlusion may be an important aid in further understanding of dentoalveolar characteristics of these conditions, as well as improving their management. Ban J Orthod & Dentofac Orthop, April 2017; Vol-7 (1-2), P.27-30